LALU LINTAS DAN ANGKUTAN JALAN TERHADAP KECELAKAAN LALU LINTAS DI JALAN RAYA (Fakultas Hukum Dehasen, 2017)
Human mobility and automobile goods are growing rapidly as a result of improved welfare and technological advances in transportation. This has resulted in increased frequency of traffic accidents with victims of drivers and road users. Users of two-wheeled vehicles are more at risk of accidents than other transportation, traffic on the road is part of the daily activities of the community. Some people do traffic activities to get to the place of activities such as offices, schools, markets, attractions and so forth. Damaged road conditions (holes) can lead to traffic accidents let alone not careful driving. Law Number 22 Year 2009 on Traffic and Road Transportation, The research method used in this research is by using normative legal research method. As a normative legal research. the implementation of Article 273 of Law No. 22 of 2009 on Road Traffic and Transportation on road accidents has not been effective. It is said that not yet effective Article 273 is a lot of accidents due to damaged roads or roads perforated but the traffic law has not been executed, when it is clearly regulated in Article 273 of Law No. 22 of 2009 on Traffic and Road Transport. Law no. 22 of 2009 is unable to reflect public discipline in traffic on the road, because it contains many unclear (unreasonable) concepts, does not have broad sociological support, does not fulfill the requirements of philosophical validity, even though it is juridically qualified.Keywords: implementation and Law Enforcement